Watching teacher candidates watch themselves: reflections on a practicum program in turkey (2010)
This article presents the findings of a study that investigates pre-service English teachers’ reflections on their teaching performance after watching their videotaped lessons in company with their university supervisor. This study, conducted during the spring semester practicum program in the 2007-2008 academic year, examines how the teacher candidates felt about their teaching while watching a video of a real lesson taught in a classroom. The findings of this study suggest that after the teacher candidates watched their own teaching with the supervisor, they made specific comments about teacher talk and about students’ participation and interest in the lesson. The findings also show that the use of video recording in the practicum program provided opportunities for reflection and helped teacher candidates evaluate their performance more critically. Key words: Non-native speaker pre-service English teachers, practicum, reflective teaching, videobased reflection sessions Este artículo presenta los hallazgos de un estudio que investiga las reflexiones de futuros profesores de inglés respecto a su desempeño docente después de haber visto con su asesor de práctica de la universidad las grabaciones de sus propias clases. Este estudio, realizado durante la práctica semestral de primavera en el periodo académico 2007-2008, examina cómo se sintieron los practicantes respecto a su forma de enseñar cuando veían un video de una clase dictada en un salón de clase real. Los hallazgos del estudio sugieren que después de que los practicantes o futuros docentes observaron en compañía de su supervisor su forma de enseñar, hicieron comentarios relacionados especialmente con la forma de hablar de los profesores y con la participación e interés de los estudiantes en la clase. Los hallazgos también muestran que la grabación en video en el programa de práctica docente generó oportunidades para reflexionar y ayudó a los practicantes a evaluar su desempeño de una forma más crítica. Palabras clave: profesores de inglés no nativos en formación, práctica docente, enseñanza reflexiva, sesiones de reflexión basadas en videos